The relationship between HRM practices and the service performance of student interns: Industry perspective - C-S. Lee; C-W. Chao; H-I. Chen (South African Journal of Business Management, 2015)
This study aims to examine the relationship between human resource management (HRM) practices and the service performance of student interns. Data were collected using a questionnaire survey that was designed to capture the perceptions of human resource managers and internship supervisors from international tourist hotels in Taiwan. The structural equation model (SEM) was used as a framework for the data analysis. The findings indicate that the service performance of student interns was greatly affected by HRM practices, including recruitment and selection, rewarding quality, and retention. The implications of this study offer preliminary insights into the industry-academia co-operation that aims to manage total quality initiatives in the hotel industry and achieve the goals of hospitality higher education. The study lays the groundwork for the development of HRM practices for student interns to cope with the changing flexible labour structure in the hotel industry.
Keywords: 650